Keterkaitan Kecerdasan Emosional dengan Kemampuan Teknik Dasar Sepak Bola Siswa Thirteens Football Academy - Zaqy Janwar Alfiansyah; Adang Suherman; Mohammad Zaky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the level of emotional intelligence, the level of basic soccer skills, and the relationship between emotional intelligence and basic skills among students aged 13–17 years at Thirteens Football Academy. The method used was a quantitative approach with a correlational design. The sample consisted of 40 students selected using a total sampling technique. Emotional intelligence was measured using a Likert-scale questionnaire covering self-awareness, self-regulation, motivation, empathy, and social skills. Basic technical skills were assessed through objective and standardized tests of dribbling, passing, and shooting. Data analysis was conducted using descriptive statistics, normality tests, and Spearman correlation analysis. The results showed that students' emotional intelligence levels were generally in the moderate to good category. Basic technical skills varied, with dribbling and passing categorized as good to very good, while shooting skills were relatively low among some students. In conclusion, there is no significant relationship between emotional intelligence and basic soccer skills (r = 0.062; p > 0.05), indicating that emotional intelligence does not significantly contribute to students’ basic technical abilities. Keywords: Basic Soccer Skills, Emotional Intelligence, Soccer, Young Athletes